Prevalensi Masalah Emosional: Stres, Kecemasan dan Depresi pada Usia Lanjut - Elizabeth Ari Setyarini; Susanti Niman; Tina Shinta Parulian; Sani Hendarsyah (Kuras Institute, 2022)
This study aims to describe the prevalence of emotional problems in the elderly in West Bandung. This research is quantitative research with descriptive design with research respondents totaling 106 people who seek treatment with physical complaints to Puskesmas DTP Gunung Halu West Bandung. The instrument for measuring the prevalence of emotional problems uses the Indonesian version of DASS 42. Data analysis using frequency distribution. The results obtained for demographic data 57.5% of respondents are female, 41.5% education level is elementary school graduates and 32.1% of respondents are housewives. The prevalence of emotional problems experienced by mild stress was 9.4%, moderate 19.8%, severe 24.5% and very severe 24.5%. The prevalence of anxiety was 19.8% at mild level, 35.8% moderate level, 34.9% severe level and 6.6% very severe level. The prevalence of depression was 16.0% at mild level, 32.1% moderate level and 22.6% severe level. The finding of emotional problems of stress, anxiety and depression in the elderly group indicates the need for mental health services at the level of primary health services such as Puskesmas.